Involvement of cyclin dependent kinase 5 and its activator p35 in staurosporine-induced apoptosis of cortical neurons - Zhang, Bai-Fang; Peng, Fang-Fang; Zhang, Wen; Shen, Han; Wu, Shao-Bo; Wu, Dong-Cheng (Acta pharmacologica Sinica, 2004)
To investigate whether cyclin-dependent kinase 5 and its regulatory protein p35 was involved in staurosporine-induced apoptosis of cortical neuronal cultures. Primary cerebral cortical neurons were exposed to 300 nmol/L staurosporine. After incubation for different time, morphological alterations were observed with phase-contrast microscopy, fluorescence microscopy, and transmission electron microscopy. DNA fragmentation was detected by agarose gel electrophoresis. The protein levels of Cdk4, p53, Cdk5, and its regulatory protein p35 following staurosporine treatment were measured by Western blotting. The Cdk5 activity was assayed for histone H1 kinase activity by autoradiography. The typical morphological changes of apoptosis were observed and the nuclear DNA fragmentation showed the characteristic "ladder" pattern after the cells were treated by staurosporine. The Cdk5 protein level increased markedly at 3 h and continued to 24 h. The p35 level increased at 3 h after being exposed to staurosporine, and decreased at 12 h. The cleavage of p35 to p25 was also detected at 12 h and increased at 24 h. There was no increase in Cdk5 kinase activity despite the increased cleavage of p35. The protein level of Cdk4 protein increased at 3 h and then decreased gradually from 6 h, but it was still higher than that in the vehicle cultures at 12 h. The p53 level decreased obviously at 3 h after staurosporine treatment and then seemed to increase at 12 h, but remained lower than that of vehicle cultures. Staurosporine-induced increase in Cdk5 protein levels and the cleavage of p35 to p25 may contribute to neuronal apoptosis.